Analisis Penilaian Guru Memakai Metode Visekriterijumsko Kompromisno Rangiranje (VIKOR) - Kharis Hudaiby Hanif; Anton Yudhana; Abdul Fadlil (Lembaga Penelitian dan Pendidikan Mandala, 2020)
Teacher Research Analysis Using the Visekriterijumsko Kompromisno Rangiranje Method (VIKOR). The process of analysis in teacher assessment can produce good teaching so that students can understand the lesson optimally. With a professional teacher who can create Human Resources (HR) who are experts. Therefore, teacher assessment plays an important role in producing human resources who are experts in their fields. But there are still many teacher assessments that are still manual, thus making the process long and inefficient. The entry of technology into various fields, especially education, can make the teacher assessment process more efficient and systematic. To facilitate the assessment of teachers can use a Decision Support System (SPK). With SPK, making weighting with complex and difficult criteria easier. There are many SPK methods to facilitate teacher assessment, in this case the author uses the SPK method is Visekriterijumsko Kompromisno Rangiranje (VIKOR). This method can facilitate the ranking of alternative professional teachers. So as to produce a decision support system to determine teacher achievement.